Beco do Fanha: aspectos históricos e materiais de um beco de Porto Alegre, 1897-1924 - Machado, Lucas Soares (2023)
In the end of the 19th century, few years after the Abolition of Slavery and the Proclamation of the Republic, the city of Porto Alegre, capital of the state of Rio Grande do Sul, had an urban structure inherited largely from the Colonial and Imperial periods. One of the most prominent characteristics of the first district, the region of the tip of the peninsula, which currently comprises the Historical Center of the city, was the existence of numerous small lanes known as alleys, which were inhabited by a diverse population, mostly poor and working-class people. This research centers in one such old lane, known popularly in that time as Fanha’s Alley. We start from a simple observation: in the beginning of the 20th century, despite the municipal authorities claiming that it was necessary to focus on one-off urban works — upgrades —, Fanha’s Alley went through great reforms, which involved the expropriation by eminent domain and demolition of the old housing and the enlargement of the street. Its inhabitants, we presume, were forced to seek new places to live, and the space was transformed, becoming occupied by modern buildings such as the headquarters of the governmental newspaper A Federação. The objective of this investigation is to list material and population characteristics of the alley, creating an in-depth picture of the space between 1897 and 1924. The period was selected because it comprises the term of office of José Montaury de Aguiar Leitão, responsible for the reforms, as well as covering the process of transformation of the lane. The study is divided in three chapters, besides an introduction and final thoughts. In the first chapter the formation and development of the alley were investigated in chronicles and city plans. The second chapter focuses on the housing and reforms, with the aid of property tax records and visual reproductions of Fanha’s Alley. In the third chapter, we sought to get to know its inhabitants; for this task, besides journalistic texts, patient admission books of the Santa Casa de Misericórdia de Porto Alegre were consulted. We concluded that Fanha’s Alley, rather than being a step in the city’s urban evolution, was a specific space, which did not survive the first decades of Republican administration.